Уявляючи травму, зображаючи жертву: до питання про (пере)визначення діаспори - Василенко, В. (Слово і Час, 2018)
У статті розглянуто проблему теоретичної (ре)концептуалізації поняття діаспори в сучасних
літературознавчих, культурологічних студіях. Крім того, досліджено питання “подвійної свідомості”
та “діаспорної ідентичності”, визначальні для розуміння діаспорних літератури й культури.
Проблемнопостановчою в розвідці виступає ідея про винайдену, уявлену природу діаспори
як своєрідної “уявленої спільноти”, що водночас є “спільнотою пам'яті”, а також порубіжний,
міжкультурний статуси діаспорної літератури. The paper deals with the issue of theoretical reconceptualization of the notion ‘diaspora’ in
contemporary literary and cultural studies. The author refers to the conceptual redefinition of the
diaspora with the idea of spatial turn in European and American cultural studies. The theory of
translocation defining the theoretical revision of the diaspora sets the understanding of the place as
the only spatial localization. The assertion that place is а geographic and not a psychological category
lies at the heart of this theory.
In addition, the paper examines the issues of ‘double consciousness’ and ‘diasporic identity’, as
they are integral to the understanding of the diaspora literature. The author considers the ‘double
consciousness’ characteristic of diaspora cultures as a result of simultaneous staying in two or more
spaces and proves the traumatic bifurcation of the ‘diaspora subject’.
The decisive idea in the paper is that of the invented, constructed essence of Diaspora as a specific
‘imaginary community’ which at the same time is the ‘memory community’, and frontier, cross-cultural
status of diaspora literature. The researcher regards the membership of the diaspora as an ‘imagined
community’, as a kind of ‘feeling at distance’, a historical need of responding to certain symbols. The
study suggests considering diaspora as a peculiar manner and form of universalizing in time and
extrapolating in space the historical and cultural experience related to trauma of the displaced nation.
It seems to be correct if one interprets diaspora not ‘externally’, but ‘from within’ – as a kind of
memory’s and imagination’s experience that demonstrates how ‘diaspora subjects’, suffering the loss of
sources (country, language, culture etc.), fix the identification associated with the source, in particular
through literary texts, artifacts of culture, commemorative practices and so on. В статье рассмотрена проблема теоретической реконцептуализации понятия диаспоры в современном
литературоведении, культурологических исследованиях. Кроме
того, исследованы вопросы о “двойном сознании” и “диаспорной
идентичности” как неотъемлемых для понимания диаспорных
литературы и культуры. Проблемнообразующей в статье является
идея об изобретенной, воображаемой сущности диаспоры как
некоем “воображаемом сообществе”, одновременно являющемся
“сообществом памяти”, а также о пограничном, межкультурном
статусе диаспорной литературы.